Inventory system for smart refrigerator / Mohd Syafiq Afifi Md Shakari - Md Shakari, Mohd Syafiq Afifi (2018)
Nowadays, the food experts especially nutrition experts have run a study of the interests of the healthy food style in spite of problems of obesity and excessive weight in the world community. Food poisoning is one of the factors and indicators that are highly emphasized by nutrition experts in maintaining the quality of food produced. Furthermore, food that is past or damaged can be used as an alternative to the agricultural sector.